Policing bodies: law, sex work, and desire in Johannesburg - Thusi, I. India (Stanford University Press, 2022)
Policing and sex work in historical perspective -- Mapping the policing of sex -- Informal policing in Rosebank -- Policing beauty -- Sex work, feminism, and policy.